Analysis of Affecting Factors of the Medical Record Service Waiting Time of Outpatient Ambulatory in Sundari Medan Hospital - Lilya Lunanda; Mappeaty Nyorong; Achmad Rifai (Newinera Publisher, 2021)
Administering outpatient medical records is required to provide excellent service to create patient satisfaction, especially with short waiting times. The purpose of this study was to determine how the factors that influence the waiting time for outpatient medical record services at Sundari Hospital, Medan.This type of research is descriptive analytic with a qualitative approach. The informants in this study consisted of 7 people, namely 4 registration officers and 3 patients who made outpatient visits. The data analysis used descriptive qualitative and the validity of the data used was data triangulation. The results show that the waiting time for outpatient medical record services for patients who register manually is longer than 60 minutes, the SOP for outpatient registration services has been implemented, it's just not done perfectly, Human resources in outpatient medical record services Sundari Hospital does not match educational qualifications, the facilities available in the outpatient medical record service at Sundari Hospital are incomplete, the technology has not been running well because the bridging system and administrative requirements for outpatients are not in accordance with Permenkes No. 28 of 2014.It is recommended that Sundari General Hospital be able to implement the requirements for outpatient administration in accordance with Permenkes No. 28/2014 and be able to implement a bridging system in outpatient services so that services can be carried out effectively and efficiently.